RUSSIAN PARTICIPATION IN THE PROJECT EUROSTUDENT V IN THE CONTEXT OF THE BOLOGNA PROCESS - Vladimir M. Filippov; Zhanna V. Puzanova; Tatiana I. Larina (Высшее образование в России)
The article discusses the results of Russia’s participation in the project on the social dimension of student life EUROSTUDENT V, which is a significant event in the framework of the Bologna process. It is the first experience of participating in such a project for Russia. Peoples’ Friendship University of Russia was responsible for the implementation of this project. The survey was realized in the shortest possible time. We used the standard for all member countries methodology and analyzed the findings. The authors highlight some social aspects of the Bologna process, give a brief description of the content, goals and objectives pursued by the project EUROSTUDENT, and describe some of the important results of Russia in the context of international comparison.